Comparison of coffee wastewater treatment technologies / Ku Muhammad Syamil Ku Azif and Nor Fariza Ismail - Ku Azif, Ku Muhammad Syamil; Ismail, Nor Fariza (2021)
Coffee is an agricultural commodity of substantial socio-economic importance that creates jobs both directly and indirectly, including employment contracts in rural areas and taxes on production. The processing of coffee can have a significant influence on the world economy. The process of coffee cherry has caused environmental issues due to discharges of huge amounts of organic waste and high concentration of contaminants in the effluent. The purpose of wastewater treatment is to protect the environment in a manner that is commensurate with public health and socio-economic concerns. Thus, an effective system or technique is proposed to meet the effluent standard for discharge of coffee wastewater from processing plant. There are different study reports for the treatment of coffee processing effluents. The reviews for the coffee wastewater treatment applied included the technology applied either in the lab experiment or tested on pilot plant simulation. The treatment methods introduced such as chemical coagulation/flocculation, advanced oxidation processes (photo-fenton oxidation), adsorption, anaerobic digestion, phytoremediation (wetland system) and ionizing irradiation (gamma radiation). All these reports stated the scientific approaches while applying treatment/management options for coffee processing. This review focuses on the most potential of treatment applied on coffee wastewater treatment based on Biochemical Oxygen Demand (BOD) reduction and Chemical Oxygen Demand (COD) reduction in coffee wastewater.